Prevalence of beta-lactamase-producing Neisseria gonorrhoeae (Colombia Medica, 1986)
From 29 men and 266 women, 291 genitourinary samples were obtained to determine the prevalence of B-lactamase-producing Neisseria gonorrhoeae (BLNG). The rapid sugar fermentation test in liquid media was used for species identification and for recognizing the prevalence of slow-growing (> 48 hours) strains (SGNG). Almost 75% of men and 21% of women were positive for NG, and 4% and 6%, respectively, had BLNG strains. They relapsed after treatment with procaine penicillin or penicillin. Also relapsed, 17% of women and 6% of men were BLNG negative. Furthermore, 20% or more of NG were SGNG, and 95% or more of the NG strains were identified in 3 or fewer hours. The presence of in vitro and or in vivo penicillin-resistant strains implies the routine use of susceptibility tests and a close follow-up.